Penggunaan Teknologi Modern Dalam Penelitian Hadits - Harie Fachrurrosi; Tajul Arifin (Yayasan Cendekia Gagayunan Indonesia, 2024)
The use of modern technology has brought significant transformations in various fields of science, including hadith research. Hadith as one of the main sources of Islamic teachings requires in-depth analyses to ensure its authenticity, validity and understanding. Modern technologies, such as big data, artificial intelligence (AI) and specialised software, allow researchers to access, organise and analyse hadith datasets more efficiently. This article discusses the application of technology in hadith research, ranging from manuscript digitisation, sanad and matan analysis, to the development of interactive hadith databases. By utilising these technologies, researchers can speed up the sanad verification process and detect patterns or anomalies in hadith texts. However, the application of modern technology also presents challenges, such as the interpretation of data that relies on specific algorithms and the need for adjustments to the traditional principles of musthalah hadith science. This study aims to explore the benefits, challenges, and future potential of the use of technology in hadith studies.